PEREMPUAN MINANG DALAM KABA CINDUA MATO KARYA SYAMSUDDIN ST. RAJO ENDAH DAN MEMANG JODOH KARYA MARAH RUSLI - Wulandari, Yosi (Universitas Muhammadiyah Surakarta, 2015)
This study aimed to describe two ways, as follows. (1) The portrayal of women Minang in Kaba Cindua Mato and Novel Memang Jodoh. (2) Comparative Depiction Minang women in Kaba Cindua Mato and Novel Memang Jodoh with Minangkabau traditional cultural values. This research was qualitative research with content analysis method. This research approach is a comparative literature with an interdisciplinary perspective. Results of this study are as follows. (1) Women Minang in kaba Mato Cindua shows Minang ancient depiction of women is synonymous with obedience to customs and understand his position as Minang women. In the novel Memang Jodoh, the portrayal of women Minang focuses on cases or unfair treatment because of the thought leaders in the community or certain customs should not lead to the referenced. (2) Comparison of Minang women in kaba Cindua Mato and novel Memang Jodoh with Minangakabau culture has provided some important notes that women Minang have some good clear position as a girl and had married.